A comprehensive study to optimize organic/inorganic ETL and HTL materials on double perovskite layer Cs2AgBiBr6 solar cells with SCAPS 1D simulator - Jabir Hakami (Results in Engineering)
Perovskite solar cells (PSCs) have garnered significant attention due to their rapid advancements in efficiency and potential to revolutionize photovoltaic technology. Despite their progress, optimizing device performance remains a critical challenge, particularly in selecting appropriate materials for key layers such as transparent conductive oxides (TCOs), electron transport layers (ETLs), and hole transport layers (HTLs). This study hypothesizes that combining inorganic ETLs and HTLs with tailored active layer thickness in double-perovskite absorbers can significantly enhance performance metrics. Using SCAPS-1D simulations, and systematically investigated the impact of various TCOs (n-ZnO, n-CuO, AZO, IZO, FTO), inorganic ETLs (TiO₂), inorganic HTLs (Cu₂O, CuI, NiO, MoO3), organic ETLs (C60, PCBM), and organic HTLs (Spiro-OMeTAD, PBDB-T) on device efficiency. The novelty of this work lies in identifying the double-perovskite Cs2AgBiBr6 as an eco-friendly, lead-free absorber and demonstrating that the configuration FTO/TiO2/Cs2AgBiBr6/NiO/Au achieves a power conversion efficiency (PCE) of 26.71 %, with an open-circuit voltage (Voc) of 1.30 V, a short-circuit current density (Jsc) of 23.72 mA/cm2, and a fill factor (FF) of 86.61 %. These results highlight the strategic potential of combining specific material choices and layer optimizations in advancing PSC performance. This study introduces a sustainable path to high-efficiency PSCs, providing valuable insights for future device engineering and material innovation.